Standard methods : (American Public Health Association, 2012)
Standard Methods for the Examination of Water and Wastewater 22nd edition offers new and updated content for over 40% of the methods and continues to be the manual that analysts, researchers and regulatory officials rely upon. Since 1905 it has been the trusted source for accurate, proven methodology for analysis of natural waters, water supplies, and wastewaters. Published by the American Public Health Association, American Water Works Association and the Water Environment Federation, Standard Methods has been reviewed and approved by a wide consensus of experts in water analysis. Methods for measuring the biological, chemical and physical attributes of waters and guidance for choosing methods for specific elements and compounds are provided.